Difficult Airway Management Algorithm in Emergency Medicine: Do Not Struggle against the Patient, Just Skip to Next Step - Jérôme Sudrial; Caroline Birlouez; Anne-Laurette Guillerm; Jean-Luc Sebbah; Roland Amathieu; Gilles Dhonneur (Emergency Medicine International)
We report a case of prehospital “cannot intubate” and “cannot ventilate” scenarios successfully managed by strictly following a difficult airway management algorithm. Five airway devices were used: the Macintosh laryngoscope, the gum elastic Eschmann bougie, the LMA Fastrach, the Melker cricothyrotomy cannula, and the flexible fiberscope. Although several airway devices were used, overall airway management duration was relatively short, at 20 min, because for each scenario, failed primary and secondary backup devices were quickly abandoned after 2 failed attempts, each attempt of no more than 2 min in duration, in favor of the tertiary rescue device. Equally, all three of these rescue devices failed, an uncuffed cricothyroidotomy cannula was inserted to restore optimal arterial oxygenation until a definitive airway was secured in the ICU using a flexible fiberscope. Our case reinforces the need to strictly follow a difficult airway management algorithm that employs a limited number of effective devices and techniques, and highlights the imperative for early activation of successive preplanned steps of the algorithm.